Persepsi Siswa Terhadap Pelaksanaan Pembelajaran PJOK Tingkat SMP Negeri Se-Kecamatan Lamongan Kabupaten Lamongan - Ahmad Fiqqi Fairuz Zabidi; Dona Sandy Yudasmara; Arief Darmawan (Program Studi Pendidikan Jasmani, Fakultas Pedagogik dan Psikologi (FPeP), 2024)
Perception in physical education is very important to know because from this perception the teacher can find out what students think of the learning being done.. The purpose of this study was to determine students' perceptions of the implementation of junior high school level physical education learning. This type of research is survey research with quantitative descriptive methods with percentage statistical calculation techniques, the sample used was 420 student respondents, data collection using instruments in the form of questionnaires. The results in this study on the implementation aspect of the study material are still many teachers who have not fully provided the material, teachers only provide a lot of game and sports material in both the Merdeka curriculum and the 2013 curriculum, models, There are several games that have been given by teachers including traditional games, invasion games, tactics games, and other games. In the aspect of assessment, students get an assessment at the end of learning in the form of skills and abilities, knowledge and portfolios. Keywords: Perception; Implementation; Physical Education Learning